A Delphi survey of health education system and interprofessional nurse' role. (April 2021) - De Luca, Enrico; Sena, Barbara; Cataldi, Silvia; Fusillo, Federica
Abstract: Background: Interprofessional education in healthcare academic and professional training is renowned to improve collaborative culture. International studies showed the existence of obstacles to establishing interprofessional collaboration and the relevance of Nurses' role in the implementation process. Aim: This study was conducted to explore interprofessional collaboration practice and education perceptions, opinions and awareness of healthcare professionals, such as academics, professional bodies representatives and multidisciplinary team managers. Methods: A multi-method two-stage approach using: 1) explorative survey and 2) Delphi group technique. A survey questionnaire focusing on interprofessionality in practice and education was administered to a convenience group of students and academics from health degree courses of three universities. Delphi group panellists were selected from a list of experts from three areas (n = 169). The iterative Delphi technique implied three-rounds to reach panel consensus (or not) about the main research topics, starting from expert panel opinions about survey results. Results: The study witnessed nurses' overall large participation (60–75%). Survey results (n = 198) showed participants' willingness to implement interprofessional education programs but controversial visions of how to implement interprofessional culture in healthcare settings. The Delphi survey showed experts' (n = 25) convergent opinions about introducing elements of communication skills and interprofessional culture into academic curricula and improving the presence of non-medical professions among the academic body. Nurses showed ambiguous positions towards concepts of autonomy and shared responsibility. Conclusions: Our study highlighted interprofessional education implementation obstacles and possible enablers. Nurses' controversial positions may reflect the struggle of the nursing profession to reach permanent academic positions and to support the shift from a medical-centric to a person-centred model of care.